Pre‐fermentative cold maceration in the presence of non‐Saccharomyces strains: effect on fermentation behaviour and volatile composition of a red wine. (13th December 2017) - Benucci, I.; Luziatelli, F.; Cerreti, M.; Liburdi, K.; Nardi, T.; Vagnoli, P.; Ruzzi, M.; Esti, M.
Abstract: Background and Aims: This study evaluated the impact of pre‐fermentative cold maceration (PCM), in the presence of two non‐ Saccharomyces yeasts, Metschnikowia pulcherrima MP 346 and Metschnikowia fructicola MF 98‐3, and of a commercial pectic enzyme, on fermentation kinetics and on the volatile composition of a Sangiovese red wine. Methods and Results: Sangiovese grape must was inoculated with MP 346 or MF 98‐3 or treated with a pectic enzyme preparation during PCM, at 5°C for 24 or 72 h. A Control wine was produced by a pure culture of Saccharomyces cerevisiae . Both non‐ Saccharomyces strains affected the initial yeast population dynamics and the persistence of S. cerevisiae at the end of malolactic fermentation. Irrespective of the duration of PCM, the inoculum of Metschnikowia strains did not influence the rate of sugar consumption or the kinetics of malolactic fermentation. The volatile composition of the final wines was evaluated with solid‐phase extraction, followed by GC/MS. The concentration of some terpenes and C13‐norisoprenoids, nerol, geraniol, 8‐hydroxy‐linalool ( cis ) and 3‐oxo‐α‐ionol, and of some esters, isoamyl lactate and ethyl isoamyl succinate, was higher in wines inoculated with Metschnikowia strains than in the Control and wine treated with pectic enzyme. Conclusions: Metschnikowia yeast strains MP 346 and MF 98‐3 affect wine volatile composition. Significance of the Study: This study shows for the first time that an inoculum of Metschnikowia strains MP 346 and MF 98‐3 during PCM is effective in modulating the volatile composition of a Sangiovese red wine.